Pengaruh Jarak Tanam dan Pemberian Jenis Pupuk Terhadap Pertumbuhan dan Produksi Tanaman Jagung (Zea mays L) Di Desa Paubekor Kecamatan Koting Kabupaten Sikka - Paulinus Yon Anderson; Yovita Yasintha Bolly (Agriculture Faculty of Flores University, 2020)
Corn is a food crop commodity that has an important and strategic role in national development. The demand for corn continues to increase in line with the increase in population as a result of the increased need for food. Increasing maize production can be done through spacing and fertilization. This study aims to determine the effect of the interaction between planting distance and fertilizer type as well as the effect of every single factor. This study was designed using a factorial randomized block design consisting of two factors, namely spacing (T) and type of fertilizer (P). Each factor consists of several levels that are combined to produce 9 treatments including T1P0, T1P1, T1P2, T2P0, T2P1, T2P2, T3P0, T3P1, and T3P2. Each treatment was repeated three times in order to obtain 27 experimental units. The observation variables included plant height and number of leaves as measured at 52 days after planting, as well as maize production per plot. Observation data were analyzed using analysis of variance (ANOVA) and continued with the LSD test at the 5% level. The results showed that the interaction between spacing and application of fertilizers had a significant effect on maize production per plot with the highest yield found in the T2P2 treatment interaction of 7.57 kg/plot. Whereas for the number of leaves and height of maize plants aged 52 DAS, the interaction between the two factors had no effect. A single treatment of spacing and application of fertilizers did not affect all the observed variables.